Discipleship in Pandemic-Era in Indonesia: a Systematic Review - Paulus Juan Setiadinata; Twin H. W. Kristyanto; Twin Yoshua R. Destyanto; Hendrik Timadius (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
The COVID-19 pandemic has had an impact on the spiritual activities of Christians in Indonesia. However, various restrictions that have arisen due to the pandemic have not stopped church leaders from carrying out their ministry, including discipleship. March 2020 to September 2021, various studies have been carried out using various research methods to discuss discipleship during the pandemic. Thus, this research aims to conduct an extensive review on discipleship during pandemic era in Indonesia from 2020 to 2021 focuses on the model, criteria of teacher, and size of discipleship recommendations. This research used a systematic review method from previous research results that were inventoried and analyzed systematically in a synthesis. The search resulted in 20 articles from various journals, which were then filtered into 12 articles focus on discussing the model, teacher criteria, and discipleship size in Indonesia during the Covid-19 pandemic. Based on the analysis, it is concluded that family and cell group-based discipleship models, taught by the parents and church servants, with a slender size (one-on-one and one-to-many with maximum 12 of size) are most recommended to be applied in this pandemic era. All type of discipleship must have an orientation towards completing the Great Commission.